STRATEGIC ADVANTAGE OF STATE-OWNED ENTERPRISES (SOEs) DEVELOPMENT POLICIES IN STRENGTHENING NAVAL ARMAMENTS - RN. YUSUF; M. MOELJADI; S. SUTRISNO; A.K. SUSILO (Journal of Defense Resources Management)
In an increasingly complex and dynamic era, the capabilities of naval armaments become crucial aspects in ensuring a country's maritime sovereignty. State-owned Enterprises (SOEs) have significant potential to act as drivers in strengthening the capabilities of naval armaments. This paper aims to delve deeper into the role and contribution of SOEs in the development of the defense industry, particularly in the context of strengthening the capabilities of naval armaments. This approach includes conceptual analysis and case studies that allow researchers to explore various aspects of policies and practices related to SOE development in the defense industry. The experts were interviewed with a total of 12 expert panels. Several important findings resulting from this analysis reinforce awareness of the crucial role of SOEs in supporting maritime defense while highlighting the potential of specific strategies in achieving the goals of strengthening naval armaments, such as Variation of Strategies Adopted by SOEs in Developing the Defense Industry, consists of Product Diversification and Technological Innovation; Collaboration with Strategic Partners; Operational Efficiency Improvement. Besides that, the success of SOE development policies in the defense industry encompasses coordinated inter-agency cooperation, investment in research and development (R&D), and supportive regulations. Further improvement and development steps in the maritime defense industry include enhancing synergy with the government through the establishment of special teams and discussion forums, boosting R&D investment through fiscal incentive programs and the establishment of innovation centers, as well as improving responsive regulations through the formation of regulatory committees and independent audits.